2015
DOI: 10.1371/journal.pone.0137890
|View full text |Cite
|
Sign up to set email alerts
|

Using Imiquimod-Induced Psoriasis-Like Skin as a Model to Measure the Skin Penetration of Anti-Psoriatic Drugs

Abstract: ObjectivePsoriasis is a chronic inflammatory skin disease and topical therapy remains a key role for treatment. The aim of this study is to evaluate the influence of psoriasis-like lesions on the cutaneous permeation of anti-psoriatic drugs.MethodsWe first set up imiquimod-induced dermatitis in mice that closely resembles human psoriasis lesions. The development of the lesions is based on the IL-23/IL17A axis for phenotypical and histological characteristics. Four drugs, 5-aminolevulinic acid (ALA), tacrolimus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 57 publications
2
39
0
3
Order By: Relevance
“…Topical application of IMQ on the mouse skin can generate human psoriasis‐like lesions with similar phenotypic, histological, and inflammatory characteristics (Lin, Yang, Chen, Kao, & Fang, ; van der Fits et al, ). That model exhibits following properties, such as increase of erythema, increase in transepidermal water loss (TEWL), decrease in skin surface pH, desquamation, epidermal hyperproliferation, the overexpression of IL‐17, IL‐23, and tumor necrosis factor (TNF)‐α, and infiltration of CD‐3 cells (Lin et al, ; van der Fits et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Topical application of IMQ on the mouse skin can generate human psoriasis‐like lesions with similar phenotypic, histological, and inflammatory characteristics (Lin, Yang, Chen, Kao, & Fang, ; van der Fits et al, ). That model exhibits following properties, such as increase of erythema, increase in transepidermal water loss (TEWL), decrease in skin surface pH, desquamation, epidermal hyperproliferation, the overexpression of IL‐17, IL‐23, and tumor necrosis factor (TNF)‐α, and infiltration of CD‐3 cells (Lin et al, ; van der Fits et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are few studies to investigate and compare the penetration behaviors of drugs and nanoparticles (NPs) formulation in psoriatic skin, the understanding of which may ultimately affect the design and development of anti-psoriatic topical formulations. In 2015, imiquimod (IMQ)-induced psoriatic skin (IMQ-psoriatic skin) was utilized to estimate the in vitro penetration behavior of drugs by Lin et al 12 for the first time, whose research demonstrated much higher penetration of drug through IMQ-psoriatic skin, than through normal skin. The study also showed that the lipophilicity of a drug dictated the permeation behaviors of the drug in IMQ-psoriatic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Imiquimod is also used to induce psoriasis to measure the skin penetration of some anti-psoriatic drugs (Lin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%